The Effect of Giving Sago Waste, Shrimp Waste and its Combination on Cholesterol Level and Growth of White Rat - T. N. Ralahalu; . Kartiarso; A. Parakkasi; K. G. Wiryawan; R. Priyanto (Jurnal Ilmu dan Teknologi Peternakan, 2011)
Cholesterol is very beneficial for the body but it needs attention when its level is increasing in the blood. The objective of the study was to determine cholesterol level and growth rate of white rat fed on ration containing sago waste, shrimp waste and their combinations. Fourty males Spraque dowley rats, aged two months with average body weight was 195.62 g, were randomly assigned to one of ten experimental treatments according to completely randomised design with four replication for each treatment. The treatments were  R0 (control diet), ASA 20 LU 0 (20% sago waste  and 0% shrimp waste),  ASA 0 LU 10 (0% sago waste and 10% shrimp waste), ASA 17.5 LU 2.5 (17.5% sago waste and 2.5% shrimp waste), ASA 15 LU 5 % (15% sago waste  and 5% shrimp waste), ASA 12.5 LU 7.5  (12.5% sago waste  and 7.5% shrimp waste),  ASA 10 LU 10 (10% sago waste  and 10% shrimp waste), ASA 7.5 LU 12.5  (7.5% sago waste and 12.5% shrimp waste), ASA 5 LU 15  (5% sago waste and 15% shrimp waste %), ASA 2.5 LU 17.5 (2.5% sago waste  and 17.5% shrimp waste).Variables measured included feed intake,  live weight gain, plasma cholesterol, HDL, LDL, triglyceride and meat cholesterol. The results showed that treatments had no (P>0.05) effects on feed intake, live weight gain, feed efficiency, plasma HDL and LDL as well as meat cholesterol. However significant differences (P<0.01) were found on plasma cholesterol and plasma triglyceride due to treatment. The lowest levels of plasma cholesterol and plasma triglyceride were observed for treatment ASA 15 LU which were 45.95 mg/dl and 43.81 mg/dl,crespectively. It can be concluded that levels of sago waste, shrimp waste and the combinations in the ration do not affect feed intake, weight gain, feed efficiency, plasma HDL, plasma LDL and meat cholesterol but it affected plasma triglycerides and plasma cholesterol of rat.